Transformasi Makna Maskawin dan Implikasinya pada Kebahagiaan Perempuan Papua di Kota Jayapura - Almince Makanuay; Margaretta Erna Setianingrum (CENDERAWASIH: Jurnal Antropologi Papua, 2025)
The study explores the transformation of dowry (maskawin) meaning and its implications for the happiness of Jayapura indigenous women in the modern era. Focusing on the Jayapura tribe in Papua, Indonesia, the research examines how the traditional concept of dowry has evolved from a primarily economic and social status symbol to a more nuanced representation of respect, love, and commitment. Traditionally, dowry was viewed as a means of economic security and social validation, but contemporary interpretations emphasize emotional value and mutual respect. The research investigates the complex relationship between dowry practices and women's psychological well-being, analyzing how social pressures and changing perceptions impact marital happiness. Using an anthropological and psychological lens, the study reveals that while dowry remains an essential cultural practice, its significance has shifted from a transactional exchange to a symbolic gesture of emotional commitment. Key findings highlight the multidimensional nature of dowry in modern Papuan society, demonstrating how it reflects broader social changes regarding gender equality, individual dignity, and interpersonal relationships. The study concludes that balancing traditional values with modern perspectives is crucial for ensuring dowry practices positively contribute to women's happiness and social recognition